2022
DOI: 10.17159/2413-3051/2022/v33i2a13190
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of household energy fuel choice in Lesotho

Abstract: The determinants of household energy fuel choice have not been studied in some developing countries, including Lesotho, despite the potential benefits such a study might have for policy design and implementation. This study uses the data collected by Lesotho’s Bureau of Statistics through a national household energy consumption survey of 2017, and a multinomial logistic regression to analyse the determinants of household energy fuel choice in Lesotho. The results indicate that the gender of the household head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
3
2
1
Order By: Relevance
“…This is expected since an increase in education level is likely to raise awareness of the health and environmental effects of using an unclean energy type [94]. However, [28] found results which are contradictory to our findings: upon disaggregation of dwelling types, [28] found that education is not important for the choice of electricity over others, such as traditional fuel for cooking. Note that in our case, the results suggest that higher education decreases electricity use for cooking.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This is expected since an increase in education level is likely to raise awareness of the health and environmental effects of using an unclean energy type [94]. However, [28] found results which are contradictory to our findings: upon disaggregation of dwelling types, [28] found that education is not important for the choice of electricity over others, such as traditional fuel for cooking. Note that in our case, the results suggest that higher education decreases electricity use for cooking.…”
Section: Discussioncontrasting
confidence: 99%
“…The estimated results show that household size, dwelling type, high level of education and dependency ratio have significant influence on households' energy choices. These results are consistent with those of Mothala et al [28], who argue that higher income levels, education, and household size are the drivers of energy fuel choice in Lesotho. Thus, policies designed to promote household job creation, effective access to electricity, and investment in education can influence the choice of clean energy use within households.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Education influences the decisions of the household to adopt modern energy fuels through the raising of awareness of the dangers of using traditional cooking fuels. This increases the opportunity cost of the collection of traditional fuels for educated household heads (Aryal et al, 2019;Rahut et al, 2019Rahut et al, , 2020Jaiswal and Meshram, 2021;Wall et al, 2021;Mothala et al, 2022). Our study findings were in agreement with the notion above.…”
Section: Implications For Education and Training In Ugandasupporting
confidence: 93%